Automation of monitoring in gas producing company; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 5 - Bogdan S. A.; Kudinov A. V.; Markov N. G.; Rodikevich S. S. (Control, computer engineeringand information science, 2007)
Заглавие с титульного листа